Caterpillars, bugs, and butterflies - Boring, Mel, 1939-; Garrow, Linda (Milwaukee, WI : Stevens, Gareth Inc., 1998)
An introduction to the world of caterpillars, butterflies, and other insects, including identification information, educational activities, and fun facts.
Based on the book, Caterpillars, bugs, and butterflies, written by Mel Boring, first published in the United States in 1996 by NorthWord Press, Inc., Minocqua, Wisconsin.
Includes bibliographical references (p. 40) and index.
850
Keywords: Caterpillars; Butterflies; Insects